La Gestión Administrativa en las Microempresas de Servicios de la ciudad de Cariamanga - Cueva Pinzón, Víctor Efrén (2024)
The present research work entitled "Administrative Management in Micro Service Enterprises in the City of Cariamanga" was carried out with the purpose of analyzing the administrative management carried out by micro service enterprises, whose main objective was to make a diagnosis of the current situation of administrative management in these businesses and through this propose an administrative management model that allows the Cariamanga entrepreneur to carry out the improvement of the administrative process. This research was exploratory and documentary, the investigative work took as a reference a study population of 202 micro service enterprises in the town of Cariamanga. To collect information, the tools of the survey were used which was applied to the owners of these micro enterprises and the realization of an interview applied to the Management, Economy and Production Promoter of the GAD Calvas. The results showed that there is poor administrative management within these businesses, as there are some problems found in each of the stages of the administrative process. In addition, it was identified that the main management styles they carry out correspond to participatory and transformational management styles. Based on the findings, a strategic management model was proposed, which was accompanied by the completion of a practical case corresponding to one of the microenterprises investigated.